The beginning and development of english boys’ schools and english girls’ schools and school libraries in the straits settlements, 1786-1941 - Lim , Peng Han (Persatuan Pustakawan Malaysia, 2010)
Throughout the nineteenth century, missionaries from Europe and America dominated the setting up of English boys’ and girls’ schools in the Straits Settlements. In 1899, there were only two known school libraries. During the1930s, more than 70% of English schools had school libraries. In 1937, 80% of English Boys’ Schools had school libraries. However, by 1935, 97% of Malay vernacular boys’ schools had school libraries since they were funded by the Government. Several factors impended the development of English school libraries. Firstly, most of these schools collected fees and were partially funded through Government grants. Secondly, there was no central book-buying agency to coordinate the importation of English books from India and Europe. The publishing and distribution of Malay books were centrally controlled by the Education Department. Thirdly, Government funding for English school libraries only began in 1939. Europe was already at war and resources were prioritized for the defense of the settlements. Fourthly, the public libraries in Singapore and Penang did not provide service to school libraries as was practiced in England. Finally, although two school library associations was established in England in 1937, the movement did not spread to the settlements.